Comparative Secretome Analyses of Mycoplasma bovis Virulent and Attenuated Strains Revealed MbovP0145 as a Promising Diagnostic Biomarker - Zhang, Hui; Hu, Guyue; Lu, Doukun; Zhao, Gang; Zhang, Yiqiu; Zubair, Muhammad; Chen, Yingyu; Hu, Changmin; Chen, Xi; Chen, Jianguo; Chen, Huanchun; Yang, Liguo; et al. (Frontiers in Veterinary Science, 2021)
Mycoplasmas are successful pathogens both in humans as well as animals. In cattle, Mycoplasma bovis (M.bovis) is known to be responsible for serious health complications including pneumonia, mastitis and arthritis. However, M. bovis pathogenesis remains unclear. Secreted proteins of M.bovis could influence infection and modify host defense signaling pathways after they enter their extracellular space in the host micro-environment. Therefore this study was aimed to compare the secretomes of M. bovis HB0801 virulent (P1) and attenuated (P150) strain and identify potential pathogenesis-related secreted proteins and biomarkers. The cells of P1 and P150 strain grew in PPLO medium to log-phase and then transferred to PBS for 2 h. Then the supernatant was analyzed by using label-free quantitative proteomics and 477 potential secreted proteins were identified. Combined with the bioinformatics prediction, we found 178 proteins were commonly secreted by P1 and P150 strain, and 49 of them were encoded by mycoplasmal core genes. Additionally, 79 proteins were found to have differential abundance between P1 and P150 strain. Of which proteins, 34 were more abundant and uniquely expressed in P1 indicating a possible association with virulence of M. bovis. Three differentially secreted proteins MbovP0145, MbovP0725, MbovP0174, as well as one equally secreted protein MbovP0481 as positive control and one protein of inner membrane MbovP0310 as negative control were respectively cloned, expressed and evaluated for antigenicity, subcellular locations and the secretion nature with their mouse antisera by western blotting and colony immunoblotting assay. Among them, MbovP0145 was confirmed to be more secreted by P1 than P150 strain, highly reactive with the antisera from naturally infected and P1 experimentally infected cattle but not P150 vaccinated calves indicating its potential as a diagnostic antigen. In conclusion, these findings may represent the most extensive compilation of potentially secreted proteins in mycoplasma species and largest number of differentially secreted proteins between the virulent and attenuated M. bovis strain to date and provide new insights into M. bovis pathogenesis and diagnosis.